1951
DOI: 10.1542/peds.7.2.230
|View full text |Cite
|
Sign up to set email alerts
|

Brock Procedure for the Relief of Pulmonary Stenosis in the Tetralogy of Fallot

Abstract: The surgical relief of pulmonary stenosis has been both direct and indirect. The indirect procedures have inherent dangers; the direct approach of Brock appears to be without these dangers and the circulation is allowed a more normal course. This approach entails an incision into the right ventricular chamber and the cutting of the stenosed pulmonary valve or the removal of obstructing tissue in the outflow tract of the right ventricle. Cyanosis is usually relieved immediately. The patient's exercise tolerance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Seven of the eight patients survived with improvement in cyanosis and exercise tolerance. Both Brock and Downing found that there was a higher than initially believed incidence of pulmonary valvular stenosis in TOF patients [25].…”
Section: Surgical Treatment—early Yearsmentioning
confidence: 99%
“…Seven of the eight patients survived with improvement in cyanosis and exercise tolerance. Both Brock and Downing found that there was a higher than initially believed incidence of pulmonary valvular stenosis in TOF patients [25].…”
Section: Surgical Treatment—early Yearsmentioning
confidence: 99%
“…in 1948, Brock described a method that relieved pulmonary truncus stenosis in cases of pulmonary valve stenosis or conus arteriosus. the procedure consisted of dilating the valve stenosis by valvulotomy using a cutting knife [15]. in 1952, lewis and taufic performed the first intracardiac procedure to close an atrial septal defect (Asd).…”
Section: Discussionmentioning
confidence: 99%
“…Closed pulmonary valvotomy was another procedure separately elucidated by Sellors in the same year [ 4 ]. The first three cases described by Brock were three children who had TOF and their procedures were undertaken via the LPA, with poor outcomes [ 5 ].The Brock’s technique was subsequently refined by reaching the pulmonary valve via a closed right ventriculotomy. However, because the background infundibular stenosis was not addressed, Brock created a punch method to resect the stenosed infundibulum, leading to better outcomes among five children [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…The first three cases described by Brock were three children who had TOF and their procedures were undertaken via the LPA, with poor outcomes [ 5 ].The Brock’s technique was subsequently refined by reaching the pulmonary valve via a closed right ventriculotomy. However, because the background infundibular stenosis was not addressed, Brock created a punch method to resect the stenosed infundibulum, leading to better outcomes among five children [ 5 ]. In 1955, he published a case study involving 150 children having TOF where the punch approach was carried out whether combined or not with pulmonary valvotomy [ 6 ].…”
Section: Discussionmentioning
confidence: 99%